Appraisal of the urban housing developments for canal restoration: a case study of Khlong Ladprao, Bangkok - Aye Yamone Htun; Pramanik, Malay; Vilas Nitivattananon; Tsusaka, Takuji W.; AIT Fellowship; AIT Alumni Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
The challenge of informal settlements in urbanization is widespread, with urban poor communities often residing in vulnerable areas like flood-prone canals and riverbanks. These locations lack essential services, worsening environmental problems. Recent efforts aim to improve these settlements through low-income housing development and canal restoration, guided by evolving policies. While past studies have explored low-income housing from different perspectives, including government assessments and tenure security, limited attention has been given to the rehabilitation of canal sided low-income housing developments. This research seeks to evaluate low-income housing upgrading initiatives in Bangkok canals. Employing a mixed-methods approach, the study involves key informant interviews, questionnaire surveys, and secondary data which were analyzed by both statistically and content analysis. The research revealed that Lad-Prao community housing project is a successful example of public-private collaboration and participatory planning that enhances urban sustainability Findings revealed that the engagement of different stakeholders, cooperation among diverse parties, subsidies and policies play a vital role to achieve the housing upgrading objectives. The house areas after upgrading, the loss of room rental business after upgrades and the community culture against the transformation are mainly found to resist the upgrades. Moreover, the information dissemination through the local residents are found as weakness in the housing developments such as lack of awareness for insurance and subsidies. Effective coordination and cooperation among diverse parties are also indispensable for overcoming challenges and achieving the project's objectives.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Innovation and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Public housing -- Thailand -- Bangkok; Housing policy -- Thailand -- Bangkok